PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS PEMUDA DAN OLAHRAGA KOTA PEMATANGSIANTAR - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
This study aims to examine and analyze the influence of leadership style and motivation on the performance of employee Youth and Sports officer Pematangsiantar City. The poor performance of the youth and sports office in responding to the challenges of the related field becomes the subject of the problem. The data was collected through questionnaires distributed and carried out in 37 Youth and Sports Officials of Pematangsiantar City. The method used in this study using research methods Structural Equation Modeling (SEM) using Partial Least Square (PLS) analysis tool. Based on the analysis results obtained that the factors that affect employee performance is the style of leadership. This is proved by the T-statistic value of leadership style variables higher than T-tables. While the motivation does not affect the performance of employees.